2021
DOI: 10.3389/fpsyg.2021.678979
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure and Rasch Analysis of the Fear of COVID-19 Scale (FCV-19S) Among Chinese Students

Abstract: The Fear of COVID-19 Scale (FCV-19S) is a new one-dimensional scale used to measure fear of an individual about the COVID-19. Given the seriousness of the COVID-19 situation in China when our study was taking place, our aim was to translate and examine the applicability of the FCV-19S in Chinese students. The sample used for validation comprised 2,445 Chinese students. The psychometrical characteristics of the Chinese FCV-19S (FCV-19S-C) were tested using Rasch analysis. Principal component analysis (PCA) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…This cross-sectional investigation was conducted in Zhengzhou city from 2–21 August 2021, when the city applied strict social distancing rules. Thus, an online data collection tool is more appropriate during the COVID-19 lockdown [ 3 , 9 , 37 ]. All the constructs in the current research were measured by structured scales that have been repeatedly used in different Chinese populations with good psychometric properties [ 15 , 37 , 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional investigation was conducted in Zhengzhou city from 2–21 August 2021, when the city applied strict social distancing rules. Thus, an online data collection tool is more appropriate during the COVID-19 lockdown [ 3 , 9 , 37 ]. All the constructs in the current research were measured by structured scales that have been repeatedly used in different Chinese populations with good psychometric properties [ 15 , 37 , 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 fear may induce a generalized negative affect [ 35 , 36 ]. For example, Chen and colleagues have collected data from 2445 Chinese students and found that fear of COVID-19 is associated with generalized feelings of strain, depression, and anxiety [ 37 ]. This finding is further replicated by research based on a sample of Chinese primary school students, middle school students, and adults [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the IRT properties assessed in the 16 reviewed papers were satisfactory. In addition, the IRT evidence was reported across different language versions, including Arabic (Jordan), 36 Portuguese, 37–39 English, 39–41 Amharic, 42 Spanish, 39 , 43 Turkish, 44 Korean, 45 Chinese, 39 , 46 Japanese, 39 Italian, 39 Urdu, 39 French, 39 Malay, 47 Bangla, 48 , 49 Persian, 12 and Romanian. 50 Therefore, the FCV-19S is verified by the findings of the present systematic review regarding its psychometric properties across different language versions.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that two studies for the Chinese sample so far were inconsistent. Specifically, one study of Chinese students, including schools and universities reported a single-dimensional structure scale [ 9 ], while another study of the general Chinese population found a two-dimensional structure scale [ 12 ]. However, our study found that the 8-item C-FCV-19s was a bi-factor model.…”
Section: Discussionmentioning
confidence: 99%
“…The Fear of COVID-19 Scale (FCV-19S) was developed in an Iranian context in 2020 and shown to have strong reliability and validity scale for assessing fears related to the coronavirus [ 7 ]. The final version of FCV-19S was a single-dimensional scale with 7 items and was shown to be significantly correlated with depression and anxiety, making it helpful for identifying these comorbid disorders [ 7 , 8 , 9 ]. Subsequently, the FCV-19S has been translated into eighteen different languages [ 8 ].…”
Section: Introductionmentioning
confidence: 99%